2021
DOI: 10.1002/anie.202114556
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Alkylation of Alkenyl Acetates with Alkyl Bromides by Nickel Catalysis

Abstract: Catalytic alkylation of stable alkenyl C−O electrophiles is synthetically appealing, but studies to date have typically focused on the reactions with alkyl Grignard reagents. We report herein a cross‐electrophile reaction of alkenyl acetates with alkyl bromides. This work has enabled a new method for the synthesis of aliphatic alkenes from alkenyl acetates to be established that can be used to add more structural complexity and molecular diversity with enhanced functionality tolerance. The method allows for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 82 publications
1
12
1
Order By: Relevance
“…These results presumably suggest that L1 Ni 0 , ( L1 )­INi II Ar, or ( L1 )­Ni I Ar species were not involved in the catalytic cycle, which is also very different from our previous works . However, when the [( L1 )­Ni I Cl] 2 catalyst was utilized, the target product can be obtained in 25% yield, which supports that the reaction was initiated with ( L1 )­Ni I Br species, rather than the L1 Ni 0 catalyst as before. As anticipated, the model reaction with this [( L1 )­Ni I Cl] 2 catalyst can proceed smoothly to give product 3 in 81% yield.…”
contrasting
confidence: 57%
“…These results presumably suggest that L1 Ni 0 , ( L1 )­INi II Ar, or ( L1 )­Ni I Ar species were not involved in the catalytic cycle, which is also very different from our previous works . However, when the [( L1 )­Ni I Cl] 2 catalyst was utilized, the target product can be obtained in 25% yield, which supports that the reaction was initiated with ( L1 )­Ni I Br species, rather than the L1 Ni 0 catalyst as before. As anticipated, the model reaction with this [( L1 )­Ni I Cl] 2 catalyst can proceed smoothly to give product 3 in 81% yield.…”
contrasting
confidence: 57%
“…Further studies established that the combination of nickel and Zn enables the coupling of alkenyl acetates with alkyl bromides (Scheme ). The reaction proceeds under very mild conditions and tolerates various functionalities, including groups that are sensitive to Grignard reagents (e.g., alkyl–Cl, RCON–H, R–CN, and RCHO). Primary, secondary, cyclic, and acyclic alkyl bromides all worked well.…”
Section: Reductive Alkylation Of Alkenyl Acetatesmentioning
confidence: 99%
“…Shu and co-workers demonstrated that alkenyl acetates can be engaged in sp 2 –sp 3 XEC with alkyl bromides, unlocking a previously inaccessible mode of reactivity (Scheme A). Oxidative addition across the C–O bond continues to present challenges due to the lack of reactivity demonstrated by unactivated alkenyl acetates.…”
Section: Part 3 Ni Catalysismentioning
confidence: 99%